2006
DOI: 10.1037/0002-9432.76.4.489
|View full text |Cite
|
Sign up to set email alerts
|

The full-frame approach: A new response to marginalized women left behind by specialized services.

Abstract: Increasing emphasis on specialization in social and mental health services leaves these systems largely unable to attend to marginalized women's complex needs, despite new models designed to ameliorate specialization's impact. In this article, the authors describe how inattention to these women's contexts leaves them ill-served and leaves programs struggling. The authors articulate a new framework of principles and practices that privileges context and community, and describe two programs that use this "Full-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 62 publications
0
68
0
2
Order By: Relevance
“…Various studies have concluded that these service networks must consist of both specialist and generalist service providers (Ellem et al, 2012;Kuosmanen & Starke, 2013;Rose, 2011;Smyth et al, 2006;Wholey & Huonker, 1993). Wholey and Huonker (1993) find that generalist service providers not only are active in their clients' various life domains, but also maintain connections to a wide variety of specialised organisations.…”
Section: Network Of Generalist and Service Agenciesmentioning
confidence: 99%
“…Various studies have concluded that these service networks must consist of both specialist and generalist service providers (Ellem et al, 2012;Kuosmanen & Starke, 2013;Rose, 2011;Smyth et al, 2006;Wholey & Huonker, 1993). Wholey and Huonker (1993) find that generalist service providers not only are active in their clients' various life domains, but also maintain connections to a wide variety of specialised organisations.…”
Section: Network Of Generalist and Service Agenciesmentioning
confidence: 99%
“…This concept is articulated in a paper describing the Full‐Frame Approach , a new response to marginalized women who are receiving social and mental health services (Smyth, Goodman, & Glenn, 2006). The authors describe how inattention to the woman's context, or the complex situational factor that has created her difficulty, leads to further marginalization and fragmentation of care.…”
Section: The Full‐frame Approachmentioning
confidence: 99%
“…Yet, there are too few services available to help low-income women deal with these realities, and those that do exist often address specific and discrete issues (e.g., housing, mental health, domestic violence), without addressing or even recognizing the complex web of difficulties within which such problems are embedded (Goodman & Smyth, in press;Smyth, Goodman, & Glenn, 2006). This article describes a qualitative content analysis of women's experiences of feminist relational advocacy (FRA), a new advocacy model designed to address the material and psychological difficulties of low-income women who are struggling with depressive symptoms.…”
mentioning
confidence: 98%